A Circularly Polarized 4×4 Microstrip Array Antenna Using Diagonal-Slot and Truncated-Patch Techniques for 2.4 Ghz WLAN Applications - Slamet Purwo Santosa; Tisya Ramdhani (Science & Technology Asia, 2026)
The use of the latest wireless telecommunications technology emphasizes the importance of antennas in improving the performance of communication systems. One recommended option is a microstrip antenna because it is lightweight, easy to integrate with the circuit, and effective in receiving circular polarization signals. This study focuses on designing, simulating, and manufacturing microstrip antennas with diagonal slots and a truncated square patch array 4×4 at a frequency of 2.4 GHz. The goal is to create microstrip antennas that are optimal for signal reception. The antennas use arrays to increase gain, while diagonal slots and truncated patches achieve circular polarization. The single-enumeration technique was used with the feed line method and simulated with CST Microwave Studio Suite 2019. The simulation results show the characteristic parameters of the 4×4 array microstrip antenna, such as working frequency 2.4 GHz, return loss -27.90 dB, VSWR 1.0984, bandwidth 55.7 MHz, gain 6.93 dB, and axial ratio 2.5 dB.